Positioning of Spoken Language by a Ukrainian Student... - Daszkiewicz, Michał (Studia Edukacyjne, 2024)
Resting on the fundamental premise that speech determines one’s educational success, the paper presents a study of how a Ukrainian student (on an exchange program in Poland) positions spoken language from her own perspective. The key idea was to diagnose and understand her approach to speaking (its subjective positioning) in a comprehensive hybrid form. To this end, two (complementary) methods were applied: an attitude scale based on positivist grounds and a semi-structured interview observing constructivist rationale. By combining the two types of findings, the study showed how spoken language is positioned by the respondent on specific universal scales, on the one hand, and in her own self-defined conceptual space, on the other hand. The mixed study shows the notion of positioning as serving and reconciling positivist and constructivist methodologies, and as demonstrating the real character of how people approach things in a twofold manner (combining a closed-ended scaling with an open self-defined categorization). In educational terms, the paper shows positioning as complementing the notion of (knowledge) construction, and on the linguistic level, it provides data on what constitutes an enhancement or an obstacle to the student’s spoken language.